Effect of Planting System and Seed Age on Yield and Yield Components of Paddy Rice (Oryza sativa L) Inpari 32 Variety - Marliani, Leni; Amalia, Lia; Budiono, Heru (Institute of Computer Science (IOCS), 2021)
The research aims to determine; (1) The effect of the interaction between the planting system and seed age on the growth and yield of rice plants, and (2) the planting system and age of the seed that gives the best yield and growth. The research was carried out in Sukamandijaya Village, Ciasem District, Subang Regency, starting from April to August 2021. The research was carried out with an experimental approach using a randomized block design (RAK) with a factorial pattern of strip plot design consisting of two factors, the first factor being a three-level planting system (tile system, jajar legowo 2: 1, and jajar legowo 4 : 1, and three levels of seed age (7 DAS, 14 DAS and 21 DAS) so that for each replication there were 9 treatment combinations and repeated three times To determine the effect of planting system treatment and seed age, analysis of variance through the F test was used, with the follow-up using Fisher's LSD/BNT follow-up test at a 5 percent. level of significance.The results showed that: (1) there was an interaction effect between planting system treatment and seed age on the yield of dry grain harvested per plot. The independent planting system affected the number of tillers per clump, the number of productive tillers, the number of grains of grain per panicle, the number of pithy grains per panicle and the weight of 1000 grains of grain. The age of the seed independently affected the number of tillers per clump, the number of productive tillers, the number of grains of grain per panicle, the number of pithy grains per panicle and the weight of 1000 grains of grain, and (2) the row planting system of legowo 4: 1 and the age of the seeds 14 days after sowing. gave the highest yield of dry grain harvest per plot, namely 7.83 kg per plot or equivalent to 8.70 tons of GKP per hectare.